Transformational leadership and its relationship with socio-emotional and moral competencies in pre-service teachers - Álamo, Mercedes; Falla, Daniel (Psychology, Society & Education, 2023)
Studies have shown that transformational leadership favours innovation, change and involvement towards improvement and problem solving, generating an atmosphere of respect and tolerance, it is considered ideal leadership in the educational sphere. Furthermore, socio- emotional and moral competences are essential for school leaders and teachers. However, there is a gap about what kind of socioemotional and moral competences can be related to a transformational leadership style in future teachers and that could be relevant information for university education, which is the purpose of this research. For this ex post facto quantitative survey research, a sample of 395 prospective teachers (81.3% female and 18.7% male) between 17 and 63 years of age (M = 21.08; SD = 3.49) was used. Statistical analyses included Student’s t-test and linear regressions. Results showed high scores in transformational leadership and a high degree of social-emotional and moral competencies. Significant gender differences were found, with girls having higher scores. Relationships were found between self-management and motivation, social awareness and prosocial behaviour, responsible decision-making and moral emotions with transformational leadership. The practical implications of these findings are discussed and concluded by pointing out the importance of working on and promoting